2013
DOI: 10.2298/tsci110510134a
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous effects of water spray and crosswind on performance of natural draft dry cooling tower

Abstract: To investigate the effect of water spray and crosswind on the effectiveness of the natural draft dry cooling tower (NDDCT), a three-dimensional model has been developed. Efficiency of NDDCT is improved by water spray system at the cooling tower entrance for high ambient temperature condition with and without crosswind. The natural and forced heat convection flow inside and around the NDDCT is simulated numerically by solving the full Navier-Stokes equations in both air and water droplet phases. Compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…According to experimental research results water droplet destruction during its motion in the high-temperature gas area is possible in case of big size of solid particle (about 50-60% of the droplet size). The established features were in good agreement with the basic concepts of the modern theory of gas-vapor-droplet flows at the phase transitions [45][46][47][48][49][50][51][52]. Developed experimental technique can significantly extend the representation of the investigations [45][46][47][48][49][50][51][52].…”
Section: Resultssupporting
confidence: 74%
“…According to experimental research results water droplet destruction during its motion in the high-temperature gas area is possible in case of big size of solid particle (about 50-60% of the droplet size). The established features were in good agreement with the basic concepts of the modern theory of gas-vapor-droplet flows at the phase transitions [45][46][47][48][49][50][51][52]. Developed experimental technique can significantly extend the representation of the investigations [45][46][47][48][49][50][51][52].…”
Section: Resultssupporting
confidence: 74%
“…M.Goodarzi [2], posed using of a specific configuration in cooling tower stack to reduce suffocation in outlet plume. Amooie & Goodarzi [5] improved the cooling tower efficiency up to 1.67% by using of heterogeneous distribution in radiators during crosswind.Ahmadikia & Coworkers [6] offered using of water spray in the inlet of cooling tower in crosswind conditions or no-wind conditions to improve cooling tower efficiency. Goodarzi & Keimanesh [7] in a research by using numerical simulation studied two other kinds of windbreakers.…”
Section: Introductionmentioning
confidence: 99%
“…Goodarzi et al [11] demonstrated that a new geometry for the dry cooling tower improved its thermal performance under windy conditions, regardless of wind direction. Ahmadikia et al [12] suggested that installing a water spray system at the heat exchanger inlet can optimize the cooling performance of the dry cooling tower, with higher water spray rates resulting in better cooling. Liu et al [13] utilized numerical simulations to investigate heat transfer performance enhancement resulting from crosswind effects at the top of a 20 m tall small NDDCT.…”
mentioning
confidence: 99%